2016
DOI: 10.1177/2325957416671410
|View full text |Cite
|
Sign up to set email alerts
|

Changing Clinician Practices and Attitudes Regarding the Use of Antiretroviral Therapy for HIV Treatment and Prevention

Abstract: As part of the HPTN065 study in the Bronx, New York and Washington, DC we surveyed clinicians to assess for shifts in their practices and attitudes around HIV treatment and prevention. ART-prescribing clinicians at 39 HIV care sites were offered an anonymous web-based survey at baseline (2010/2011) and at follow-up (2013). The 165 respondents at baseline and 141 respondents at follow-up had similar characteristics: almost 60% were female; median age was 47 years; two-thirds were physicians, and nearly 80% were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“… 1 Universal and early treatment are now recommended for all HIV-positive individuals to lower HIV transmission and improve survival. 2 , 3 , 4 , 5 , 6 Clinicians now recommend early treatment, 7 and these advances have led to an increase in life expectancy among HIV-positive individuals in the United States. 8 Using a cross-sectional approach, 2014 US national surveillance data found that approximately 57% of HIV-positive individuals demonstrated viral suppression.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Universal and early treatment are now recommended for all HIV-positive individuals to lower HIV transmission and improve survival. 2 , 3 , 4 , 5 , 6 Clinicians now recommend early treatment, 7 and these advances have led to an increase in life expectancy among HIV-positive individuals in the United States. 8 Using a cross-sectional approach, 2014 US national surveillance data found that approximately 57% of HIV-positive individuals demonstrated viral suppression.…”
Section: Introductionmentioning
confidence: 99%
“…The study included several components designed to expand HIV testing, to evaluate the effectiveness of financial incentives for linkage to care and viral suppression and a computer-based prevention intervention for HIV-positive persons in care, and surveys of providers and patients to assess attitudes about antiretroviral therapy for prevention. [1618] We describe here the expanded hospital testing component, which sought to achieve the universal offer of HIV testing during ED visits and inpatient admissions.…”
Section: Introductionmentioning
confidence: 99%
“…In these predominately high‐income countries, variation in site‐level introduction may reflect heterogeneous health policy environments, decentralized health systems, and a higher proportion of private‐sector sites operating autonomously. Earlier site‐level adoption of Treat All in these countries may reflect the feasibility of expanding HIV treatment, given lower HIV prevalence, higher‐resourced health systems, and stronger logistics systems in these settings , whereas later site‐level introduction in these countries may reflect barriers, such as gaps in providers’ knowledge, or lingering provider concerns about potential negative consequences, such as the emergence of resistance, treatment side effects, increased sexual risk‐taking and lack of patient‐readiness . In contrast, there was less between‐site variation in time‐to‐implementation in countries adopting Treat All after WHO's 2015 recommendation, especially in low‐/lower‐middle‐income countries supported by PEPFAR and/or the Global Fund, suggesting that site‐level roll‐out of Treat All may be more uniform in countries receiving support from these and other donors .…”
Section: Discussionmentioning
confidence: 99%